Changes in Chlorophyll a fluorescence and DNA as a plant response to UV-B radiation in Gnaphalium vira-vira - Cuadra Burgueño, Pedro Osvaldo; Fajardo Morales, Victor Manuel; Pimentel, Paula; Moya-Leon, M. Alejandra; Herrera, Raul (My University, 2022)
Ozone depletion at southern latitudes has recently increased the fluence of ultraviolet-B (UV-B) radiation striking the ground. This phenomenon has sparked much interest in unravelling the effects of this harmful radiation on living systems. UV-B radiation triggers several responses that affect plant physiology, morphology and biochemistry. In this study, the effect of supplemental UV-B radiation on DNA profile and chlorophyll a (CHl a) fluorescence characteristics were analyzed. An increase in the genetic variability of irradiated plants was observed in the Inter Sequence Simple Repeats products. The effect on photosynthesis was studied through fluorescence emissions. The obtained data showed that photochemical quenching (qP) decreased in irradiated plants. This effect may be attributed to a decrease in the number of open reaction centers of photosystem II (PSII) as suggested by the decreased values of minimal and maximal fluorescence. Likewise, non-photochemical quenching (NPQ) increased in both control and irradiated groups, but treated plants presented lower NPQ values than controls. The heat dissipation mechanism was also altered, probably due to a decrease i in the yield of the maximal fluorescence in light-adapted leaves (Fm acute accent ). According to these findings, UV-B radiation affects the CHl a fluorescence mechanisms and modifies DNA profile. Consequently, these changes influence the yield and growth of plants, which is an important consideration given the current climate change situation.
Keywords: antarctic; sii reaction center; dna damage; photochemical and non-photochemical quenching